MAIN ADVANTAGES OF CLUSTER APPROACH IN EDUCATION - Umirova Dilafruz Abdurasulovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article highlights the main advantages of the cluster approach in education and the cluster approach in the training of highly qualified specialists, the characteristics of the cluster approach that ensure interaction and increase the competitiveness of educational organizations in the context of the cluster approach.